Ekstrak Umbi Rumput Teki (Cyperus Rotundus) Sebagai Antibakteri Terhadap Staphylococcus Epidermidis Dan Propionibacterium Acnes - Nurjanah, Siti; Rokiban, Akhmad; Irawan, Erdy (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2018)
The tuber of cyperus rotundus are used to tradisional medicine. C. rotundus known to contain compounds of secondary metabolites such as alkoloids, sineol, pinene, siperon, rotunal, siperenon, siperol, tannins, flavonoids and scientifically it has been believed to have antimicrobial activity. Empirically this plant are used as an antibacterial, antitumor, anticancer, and antiallergic. The purpose of this study were determining the inhibition of extract of Cyperus rotundus against tubers of Staphylococcus epidermidis and Propionibacterium acnes. In this study C. rotundus extracted by maceration using 70% ethanol. The extracts tested against S. epidermidis and P. acnes using disc blank method. The results obtained from the mean diameter of the inhibition zones of exstract at concentrations of 20%, 40%, 60%, 80%, and 100% on S. Epidermidis 8.03 mm, 11.43 mm, 15.04 mm, 15.83 mm and 19.98 mm respectively and P. acnes 11.59 mm, 13.35 mm, 17.17 mm, 20.44 mm, and 30.08 mm respectively Aquades used as negative control and erythromycin used as positive control. Testing were continued by determining the Minimum Inhibitory Concentration (MIC). The result of MIC for S. epidermidis was 15% and P. acnes was 11%. The analysis showed that the antibacterial activity of the tubers extract is bacteriostatic for S. epdermidis and bacterisid for P. acnes.